2010
DOI: 10.1590/s0100-204x2010001200008
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de míldio no cultivo protegido de videira de mesa 'BRS Clara'

Abstract: Resumo -O objetivo deste trabalho foi avaliar a eficiência da cobertura de plástico e da tela antigranizo associadas, ou não, a programas de aplicação de fungicidas, no controle de míldio na cultivar de uva de mesa BRS Clara, sob condições de produção das safras normal e temporã do norte do Paraná, e analisar a influência de variáveis micrometeorológicas no progresso da doença. Foram conduzidos experimentos em duas safras normais (setembro a dezembro) e duas safras temporãs (janeiro a maio) nos anos 2008 e 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 9 publications
1
19
0
8
Order By: Relevance
“…In subtropical areas, grape harvest can occur during high favorable conditions for the development of postharvest fungal diseases, which can limit the long-distance transportation of fresh grapes [8][9][10]. Among fungal diseases, gray mold, caused by Botrytis cinerea Pers.…”
Section: Introductionmentioning
confidence: 99%
“…In subtropical areas, grape harvest can occur during high favorable conditions for the development of postharvest fungal diseases, which can limit the long-distance transportation of fresh grapes [8][9][10]. Among fungal diseases, gray mold, caused by Botrytis cinerea Pers.…”
Section: Introductionmentioning
confidence: 99%
“…The need to increase productive sustainability and the pressure of consumers groups has forced the reevaluation of such models of conventional production (FADINI, LOUSADA, 2001). Following this concept, the use of plastic cover represents an alternative for grape production, especially in warm and Organic production of red wine grapes under plastic cover... humid climates, because this system could avoid the wetting of upper plant parts and, consequently, decrease pathogenic fungus, allowing the reduction or elimination of chemical fungicides (GENTA et al, 2010). Chavarria et al (2007) reported that during maturation of 'Moscato Gallo' grapes, there was a decrease of decay incidence between 57.6 and 84.5% due to plastic covers.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the use of plastic cover occurred in Paraná (Genta et al, 2010) and Sao Paulo (Lulu et al, 2005;Pedro Junior, 2006;Colombo et al, 2011). According with information of the Agricultural Cooperative of Juazeiro -BA (ACJ), the use of the plastic cover in the Sao Francisco River Valley region has been taking place since 2000, to protect the vineyards of rain and prevent the occurrence of cracks berries throughout the period of grape maturation and harvesting.…”
Section: Introductionmentioning
confidence: 99%